PA.51 Indications for the Use of High Vaginal Swabs in Obstetrics: A Quality Improvement Project. (9th June 2014) - Davis, CAR; Mustafa, H; Gibb, P
Abstract : Over 17, 000 high vaginal swabs are processed by the medical microbiology laboratory at the Royal Infirmary of Edinburgh each year. The majority of these high vaginal swabs are reported as negative. In most cases of positive results, the diagnosis could be made clinically (e.g. Candidiasis, Bacterial Vaginosis (BV)) and their presence does not indicate a sexually transmitted infection (STI). As such this represents a potentially significant waste of time and resources. All high vaginal swabs taken during the month of august in obstetric triage and assessment were examined for their clinical indication as well as their culture and treatment outcome. The results showed that as expected the majority of swabs were culture negative and only a minority of the culture positive swabs required treatment. Further analysis also revealed that while the majority of swabs taken were done so based on an appropriate clinical indication 18% of swabs were not. The most common indication quoted was abdominal pain with no signs or symptoms of infection evident or recorded. As all these swabs were culture negative they did indeed represent a waste of laboratory time and resources and as a result a formal guideline on indications for the use of high vaginal swabs was produced with the aim of reducing unnecessary investigations.